Dietary patterns and risk of colorectal cancer: a comparative analysis. (14th December 2022) - Wang, Peilu; Song, Mingyang; Eliassen, A Heather; Wang, Molin; Giovannucci, Edward L
Abstract: Background: Although several dietary patterns have been associated with incident colorectal cancer (CRC), it is unclear which diet is optimal. Methods: Participants included 48 409 men and 169 772 women from three USA-based prospective cohort studies. We compared the associations of 18 dietary patterns with CRC risk, including two reference scores. The reference scores were derived based on the dietary recommendations for cancer prevention and CRC-specific dietary risk factors mentioned in the 2018 World Cancer Research Fund/American Institute of Cancer Research (WCRF/AICR) Third Expert Report. Multivariable Cox proportional hazards models were fitted to estimate hazard ratios (HRs) and 95% CIs. Results: Most dietary patterns showed moderate correlations with the WCRF dietary score (absolute values of Spearman correlation coefficients: 0.45–0.63), except the Plant-based diet index, low-carbohydrate diets, the Empirical dietary index for hyperinsulinemia (EDIH) and Empirical dietary inflammation pattern (EDIP). HR for the 10th–90th percentile difference in the score was 0.86 (95% CI: 0.78–0.94) for the Dietary Approaches to Stop Hypertension score (DASH), 1.15 (1.06–1.26) for Western dietary pattern, 1.20 (1.10–1.31) for EDIH and 1.23 (1.13–1.34) for EDIP. These associations between patterns and CRC risk persisted after adjusting for the two reference scores. Conclusions: Although further research is needed to improve the WCRF/AICR dietary recommendations, our comprehensive assessment of dietary patterns revealed that the DASH, Western dietary pattern, EDIH and EDIP may be the most relevant diets for preventing CRC.